First Detection of the Invasive Mosquito Vector Aedes albopictus (Diptera: Culicidae) in Benin, West Africa, 2021. Issue 3 (7th April 2022) - Yadouleton, Anges; Hounkanrin, Gildas; Tchibozo, Carine; Bialonski, Alexandra; Schmidt-Chanasit, Jonas; Jöst, Hanna
Abstract: Aedes albopictus (Skuse) is native to Southeast Asia and has colonized tropical and temperate regions worldwide in the last three to four decades. In Africa, data on its distribution is incomplete. Most studies having focused on the abundance, competition to other species, and phylogenetics of this vector are from the central African region. Here, we report the first detection of Ae. albopictus in Benin, West Africa. A total of 13 specimens were collected during the study period in 2021. The phylogenetic analysis of a cytochrome oxidase c subunit I gene fragment revealed a close relationship to populations from tropical India. Because of its close geographical proximity to areas where it has been found, it is assumed that the species was introduced several years before and is currently widely distributed in Benin. Additional studies are needed to explore its distribution, expansion range, and competitive effects on native species.